Roads, social severance and elderly pedestrians : a Palmerston North pilot study: a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University - Halsted, Elizabeth Louise (Massey University, 1999)
Social severance, both physical and psychological, refers to the negative social impacts caused by roads and their traffic. Social severance falls most heavily upon groups of people with limited mobility, including the elderly. This thesis examines the extent to which social severance is experienced by elderly pedestrians. A research framework is developed and its utility for identifying and measuring social severance effects on elderly pedestrians is assessed in relation to a pilot study carried out in Palmerston North. A literature review was undertaken on how the elderly are affected by social severance, as users of both roads and vehicles. Following this, Tate's (1997) framework is adapted for identifying and measuring social severance effects on elderly pedestrians. First, questionnaires were completed by elderly people living in Palmerston North, the majority of whom were from the Palmerston North Senior Citizens Club. Second, semi-structured interviews were conducted with 12 elderly pedestrians drawn from the questionnaire respondents. Findings of both research methods were then analysed. It was found that social severance is experienced significantly by elderly pedestrians in everyday living in relation to established residential streets. The data suggests psychological severance is experienced more by elderly pedestrians when they and their neighbours have lived and owned their homes for a lengthy period of time. Income, health, disability and lack of choice are identified as factors constraining mobility and access to facilities and social activities. However, this is exacerbated by the lack of knowledge on the part of elderly pedestrians about the facilities and transport services available to them. The mobility and accessibility of elderly pedestrians is also constrained by inadequate public transport, poor road design and, poor crossing facilities. Safety and confidence of elderly pedestrians when walking is decreased at certain times of the day, by people's driving behaviour, lack of lighting and poor road design. These findings point for the need for social severance to be given more weight when improvements to existing road networks as well as new road developments are proposed.
Keywords: New Zealand Palmerston North; City traffic; Social conditions Older people; Roads -- Social aspects; Effect of roads on social participation; Effect of traffic engineering on social participation